Broken Windows, Broken Promises: Grief, Privilege, and Hope in the Mythical Post Racial, a Call and Response. (September 2016) - Sharp-Grier, Martina L.; Martin, Jennifer L.
We present our narrative as an exercise in Critical Performance Pedagogy: Culture Jamming. It is our contribution to the #BlackLivesMatter movement. Our collective voice, which is framed as a reflexive layered narrative, is offered to both incite introspection and provide a glimpse into the lived understanding of the "Other[ed]." The call and response-inspired exchange represents indigenous method, and is a challenge to the hegemony regarding the narrative voicing of African Americans. It frames the frustration and subsequent activism of stigmatized people and offers a response to their narrative by a White educator poised to institute culturally responsive pedagogy. It is presented as research method, commentary, and call to action, in this not-so-post-racial milieu.